Questioning strategy in process writing approach : Evidence for idea extension in introductory paragraph - Mohd Khairi, Razali; Azwin Arif, Abdul Rahim; Nor Yazi, Khamis; Mohammad Musab, Azmat Ali (2022)
Many students at the tertiary level find it hard to have ideas in the introductory paragraph. One way to overcome that issue is by applying a questioning strategy. The convergent parallel design of qualitative and quantitative methods is adopted to collect data through a need assessment survey, diagnostic tests, and face-to-face interviews. Process writing activities were designed after the needs assessment survey findings, and pre-test scores showed the necessity to introduce the questioning strategy to the experimental group. On the other hand, the control group was formed to contrast the strategy with free writing activities. Tests scores of the two groups after 18 weeks of the writing process activities were compared using Klimova’s (2014) writing assessment criteria. The scores of diagnostic pre and post-tests on ideas extension showed that most of the experimental students’ scores were better than those in the control group. The questioning strategy in the process writing approach improved the students’ ideas for the introductory paragraph compared to free process writing. The strategy’s effectiveness could be extended to help students develop ideas and organise content paragraphs.